Mega cultural events: Does attendance affect residents’ perceptions of a city’s identity? - Santos, José de Freitas (2015)
Events are frequently planned with a goal of attracting tourists to a destination. However, studies about the impact of a mega cultural event on residents’ identity are scarce. This research is based on the premise that hosting a mega cultural event can, to a significant degree, change a few of the attributes of the city’s identity as it is perceived by its residents. Specifically, the objective of the study is to identify the attributes of the city and compare the differences found between different groups of residents (attendees vs. non-attendees) before and after a mega cultural event. For this purpose, we focus our attention on Guimarães the ECOC 2012 (2012 European Capital of Culture) and the perceptions of the residents of this city. Several significant findings are reported and their implications for event managers and public policy administrators presented, along with the limitations of the study.